When Choice Makes Sense: Menthol Influence on Mating, Oviposition and Fecundity in Drosophila melanogaster - Abed-Vieillard, Dehbia; Cortot, Jérôme (Frontiers in Integrative Neuroscience, 2016)
Abstract The environment to which insects have been exposed as larvae and adults can affect subsequent behaviors, such as mating, oviposition, food preference or fitness. Experience can change female preference for oviposition, particularly in phytophagous insects. In Drosophila melanogaster, females avoid laying eggs on menthol rich-food when given the choice. Exposure to menthol during larval development reduces this aversion. However, this observation was not reproduced in the following generation. Recently, we have shown that oviposition-site preference (OSP) differs between wild-type D. melanogaster lines freely or forcibly exposed to menthol. After 12 generations, menthol “forced” lines still exhibit a persistent aversion to menthol whereas ‘free-choice’ lines show a decreased aversion for menthol rich-food. Here, we compare courtship behavior, mating and female fecundity in "forced" and "free-choice" lines, raised either on menthol rich-food (Menthol-lines) or on menthol-free food (Plain-lines). "Forced” males did not discriminate between decapitated virgin females of the two lines. They courted and mated with intact females of both “forced” lines in a comparable rate. However “forced” M-line males did mate significantly more rapidly with “forced” M-line females. In the “free-choice” procedure, P-line males show a similar pattern as “forced” males for discrimination ability and courtship. M-line males courted significantly more M-line females. Both ‘free-choice’ lines males mated significantly more with females of their own line. Female fecundity was assessed during ten days in ‘free-choice’ lines. Menthol-line females laid more eggs during the first four days than female Plain-lines and parental control-line. The total number of eggs laid during the first ten days of female adult life is comparable in M-line and parental control line. However, Menthol-line females laid eggs earlier than both parental control and Plain-lines. Our findings show that in Drosophila melanogaster, as for OSP, mating and fecundity are more rapidly influenced when flies have a choice between alternative resources compared to flies permanently exposed to menthol.